Analisis Kelayakan Bisnis Ditinjau Dari Aspek Pemasaran ( Studi Kasus Pada Usaha Gula Merah Aren ) - Patrisia, Eka Salsa; Hardinata , Dodi; Sachanovrissa , Silke; Arieantara , Yudi (Jurnal Pusat Manajemen, 2024)
This research aims to assess the feasibility of the palm brown sugar business from the marketing aspect in Tanjung Aur 1 Village, Kec. Pino, Kab. South Bengkulu. A qualitative approach was used with observation,binterview and evaluation methods with brown palm sugar business owners. This research evaluates seven aspects of marketing, namely product, price, place, promotion, human resources, process and company image. The research results show that palm brown sugar products have high quality and various types. The prices offered are competitive, although adjustments need to be made to compete with other products on the market. Sales points include homes and local markets, while promotions are carried out through social media and direct word of mouth. Human resources are limited to the owner and his family, but are quite effective for the current business scale. The production process is running well, despite challenges in modern management and long manufacturing times. In conclusion, this palm brown sugar business has the potential to develop further with appropriate marketing strategy adjustments.